SUPPORTING CHRONIC DISEASE MANAGEMENT WITH TELEMEDICINE: AN EXAMINATION THROUGH TECHNOLOGY ACCEPTANCE MODEL - Listiani, Ade Irma; Lontoh, Eugene; Novalinda, Ruth Christine; Tamara, Dewi; Furinto, Asnan (Universitas Multimedia Nusantara, 2024)
Abstract - This research was conducted to explore how telemedicine can assist people with chronic illnesses by examining the relationship between healthcare needs, social influence, and healthcare access by employing the Technology Acceptance Model (TAM). The study was conducted across 144 participants with varying healthcare needs and social backgrounds. The findings revealed that healthcare needs had a significant and positive impact on the perceived usefulness of telemedicine. Social influence was identified as a key factor that positively affected both the perceived usefulness and ease of use of telemedicine. Moreover, the overall acceptance of telemedicine among people with chronic illnesses was positively influenced by perceived usefulness and ease of use. The healthcare access that would influence the acceptance of telemedicine did not have a significant moderating effect on the acceptance of telemedicine as initially hypothesized. The study's conclusions provide useful information for healthcare professionals, policymakers, and health tech businesses. This helps to enhance telemedicine adoption and develop effective implementation strategies among those who manage chronic diseases. Keywords: Chronic Diseases; Healthcare Access; Healthcare Needs; Technology Acceptance; Technology Acceptance Model; Telemedicine